Identification of Mycobacterium Sp. As An Alfalfa Root Bacterial Endophytes Using 16s RRNA Gene Sequence Analysis - ALI DELJOU; MIRKAVE MOUSAVIEHZADE; ABOLGHASEM GHASEMI; HESHMATOLLAH RAHIMIAN (International Journal of Pharma and Bio Sciences, 2010)
Endophytic bacteria, for all or part of their life cycle, invade the tissues of living plants and cause unapparent and asymptomatic infections within plant tissues. It has been shown that they could have some benefits for host plants when reintroduced, like control of fungal or bacterial diseases, nitrogen fixation, etc. Some of the plant endophytic and pathogenic bacteria have been found in animal tissues and vice versa. Mycobacteria are gram positive actinobacteria widely distributed in water and soil and cause diseases in animal and human beings. In this study, for the first time, Mycobacterium sp. is introduced as bacterial endophyte of alfalfa following investigation of alfalfa wilt disease. We isolated microorganisms from the vascular tissues of surface sterilized roots and identified them as Mycobacterium sp. using 16S rRNA gene full and partial sequence analysis.